Bank ownership around the world - Ugo Panizza (Graduate Institute of International and Development Studies, 2023)
This paper builds a dataset on bank ownership that covers more than 6,500 banks in 181 countries (59 low-income economies, 72 middle-income economies, and 50 high-income economies) over 1995-2020. I show that until 2010, there was a reduction in state-ownership of banks and an increase foreign ownership. However, the Global Financial Crisis interrupted or reversed these trends. At the country level, the relationship between bank ownership and each of GDP growth and financial depth is mixed: regressions with country fixed effects indicate that the presence of foreign-owned banks is positively associated with future economic growth and state-ownership is negatively but not robustly associated with future financial depth. Bank-level regressions show that state-owned banks are less profitable and have a higher share of non-performing loans than their private (domestic or foreign) counterparts. State-owned and foreign-owned banks located in developing economies pay and charge lower interest rates than their domestic private counterparts. There is also evidence that state-owned banks stabilize credit in the presence of domestic shocks while foreign banks amplify external shocks. In terms of domestic shocks, foreign banks are not significantly different from their domestic private counterparts.
Keywords: G21; G28; G32; F21; F36; O16; 330; State-owned banks; Foreign-owned banks; Economic growth; Financial depth; Non-performing loans; Credit cyclicality